F8 gene inversion and duplication cause no obvious hemophilia A phenotype - Li, Shaoying; He, Jianchun; Chu, Liming; Ren, Shuai; He, Wenzhi; Ma, Xiaoyan; Wang, Yanchao; Zhang, Mincong; Kong, Lingyin; Liang, Bo; Li, Qing (Frontiers in Genetics, 2023)
Hemophilia A (HA, OMIM#306700) is an X-linked recessive bleeding disorder caused by defects of the F8 gene, which encodes coagulation factor VIII (FVIII). Intron 22 inversion (Inv22) are found in about 45% of patients with severe hemophilia A. Here, we reported a male without obvious hemophilia A phenotype, but bearing an inherited segmental variant duplication encompassing F8 as well as Inv22. The duplication was approximately 0.16Mb and involved exon 1 to intron22 of F8. This partial duplication and Inv22 in F8 was first found in the abortion tissue of his older sister with recurrent miscarriage. The genetic testing of his family revealed that his phenotypically normal older sister and mother also had this heterozygous Inv22 and a 0.16 Mb partial duplication of F8, while his father was genotypically normal. The integrity of the F8 gene transcript was verified by sequencing of the adjacent exons at the inversion breakpoint, which explained why this male had no phenotype for hemophilia A. Interestingly, although he had no significant hemophilia A phenotype, the expression of C1QA in his mother, sister, and himself was about only half of that in his father and normal population. Our report broadens the mutation spectrum of F8 inversion and duplication, and its pathogenicity in hemophilia A.